A Development of Database Driven Inventory Management for Saudi Small Enterprises - Yousef, Alqahtani Ebtisam (2011)
Nowadays, the changing in business operations among customers is facing huge challenges due to the new competition of adopting technology by businesses today. Most of these challenges can be found among the Saudi Small Enterprise companies (SSEs), which reflects the needs of developing a suitable system for managing and optimizing the business activities in these companies. A number of difficulties were reported during the process of inventory management, which recognized to be one of the most critical operations for any SSEs. Hence, integrating new technology could help to overcome the SSEs difficulties in performing and managing its operations in reliable way. Meanwhile, this research aimed to develop an inventory management system for simplifying and managing SSEs operations in a flexible way based on the utilization of multi agent interface that could add extra advantages in operating the business deals over the internet.